Mewujudkan UMKM yang Berlegalitas: Pendampingan NIB bagi UMKM Rera Nastar di Desa Ental Sewu - Akhmada Jamaluddin Al-Afgani Al-Afgani; Fika Wardah Al Musyafa'ah; Refa Dwi Ananta; Moch Zacky Mubarok; Adiftia Maulana; Muhtarom; Nafia Ilhama Qurrotu'aini (Journal of Science and Social Development, 2025)
The assistance program for obtaining a Business Identification Number (NIB) was conducted to assist Rera Nastar, a pastry business owned by Mrs. Ulfatun Ni'mah, which has been established since 2019 in Ental Sewu Village, Buduran, Sidoarjo. This assistance was motivated by the low understanding of MSMEs regarding the function and procedures for submitting a NIB through the OSS-RBA system. The assistance process was carried out through several stages, namely planning, preparation, and direct registration practice. However, there were obstacles when filling out the AMDAL (Environmental Impact Assessment) which could not be submitted, so the registration had to be repeated several times. After conducting several evaluations and data adjustments, Rera Nastar's NIB was finally successfully issued on November 27, 2025. The assistance results showed an increase in business understanding, as well as the successful completion of the legality process. This activity provided significant benefits in raising awareness about business legality and preparing MSMEs to officially develop their businesses.